Energy Self-sufficiency of Farms in Kosovo: An Application of Swot and Pest Methodology - Pestisha, Albiona; Bai, Attila (Acta Carolus Robertus, 2024)
Energy stands as a vital stimulus for societal, economic, and technological progress globally. Energy self-sufficiency has emerged as a strategic goal for many nations, driven by concerns over energy security, sustainability, and economic resilience. Within this context, Kosovo relies heavily on fossil fuels and insufficient alternative energy sources, making it tough to achieve self-sufficiency in agriculture. The agricultural domain relies extensively on energy to power various of its operations, rendering energy self-sufficiency a compelling avenue for addressing associated challenges. By serving as a benchmark that evaluates the current status and charts a prospective roadmap for fostering the renewable energy sector in Kosovo, the SWOT analysis delineates internal strengths and weaknesses alongside external opportunities and threats. Emphatically, the study highlights the indispensability of public awareness campaigns, capacity-building initiatives, and streamlined access to financial resources. Additionally, the study emphasizes the pivotal role of project preparation, credit accessibility, financing costs, and equity financing facilitation in bolstering the nation’s prospects for realizing its energy self-sufficiency objectives, otherwise Kosovo may struggle to meet its energy goals.